The DESI N-body simulation project – I. Testing the robustness of simulations for the DESI dark time survey. Issue 2 (22nd July 2022) - Grove, Cameron; Chuang, Chia-Hsun; Devi, Ningombam Chandrachani; Garrison, Lehman; L'Huillier, Benjamin; Feng, Yu; Helly, John; Hernández-Aguayo, César; Alam, Shadab; Zhang, Hanyu; Yu, Yu; Cole, Shaun; et al.
ABSTRACT: Analysis of large galaxy surveys requires confidence in the robustness of numerical simulation methods. The simulations are used to construct mock galaxy catalogues to validate data analysis pipelines and identify potential systematics. We compare three N -body simulation codes, abacus, gadget-2, and swift, to investigate the regimes in which their results agree. We run N -body simulations at three different mass resolutions, 6.25 × 10 8, 2.11 × 10 9, and 5.00 × 10 9 h −1 M⊙, matching phases to reduce the noise within the comparisons. We find systematic errors in the halo clustering between different codes are smaller than the Dark Energy Spectroscopic Instrument (DESI) statistical error for s 20 h^-1 Mpc in the correlation function in redshift space. Through the resolution comparison we find that simulations run with a mass resolution of 2.1 × 10 9 h −1 M⊙ are sufficiently converged for systematic effects in the halo clustering to be smaller than the DESI statistical error at scales larger than 20 h^-1 Mpc. These findings show that the simulations are robust for extracting cosmological information from large scales which is the key goal of the DESI survey. Comparing matter power spectra, we find the codes agree to within 1 per cent for k ≤ 10 h Mpc −1 . We also run a comparison of three initial condition generation codes and find good agreement. In addition, we include a quasi- N -body code, FastPM, since we plan use it for certain DESI analyses. The impact of the halo definition and galaxy–halo relation will be presented in a follow-up study.